Qualitative study on nurse preceptors’ preparedness, roles and familiarity with the basic principles of teaching and learning in a district hospital in Ghana - Dorothy Serwaa Boakye; Vida Maame Kissiwaa Amoah; Edward Appiah Boateng; John Antwi; Joyce Yeboah; Jennifer Owusu (BMJ Open)
Objective This qualitative study explored the experiences, preparedness, instructional practices and roles of preceptors supervising nursing students in a clinical setting.Design Exploratory descriptive study employing semi-structured interviews.Setting A district hospital in the Kumasi Metropolis accredited for training nursing students in clinical practice.Participants 12 nurse preceptors, each holding at least a Bachelor of Science in Nursing.Major findings Findings revealed gaps in the preparation of preceptors and a lack of a clear definition of preceptors’ roles and responsibilities from the outset, contributing to feelings of under-preparedness. While demonstrating inherent strengths like using probing questions, prompting techniques and assuming multifaceted roles, including role modelling, coaching and teaching, preceptors expressed uncertainty about over-reliance on passive demonstration-based teaching. Environmental barriers like noise concerns hindered the adoption of more interactive, student-centred pedagogies.Conclusion The study highlights the need for comprehensive preceptor training programmes that provide robust onboarding, set clear expectations and equip preceptors with diverse evidence-based teaching methodologies tailored to healthcare contexts. Continued research involving larger samples, multimodal data and stakeholder perspectives can inform ongoing programme refinement.